Nitrogen oxides and ozone in urban air: A review of 50 plus years of progress. Issue 6 (23rd July 2020) - Erickson, Larry E.; Newmark, Gregory L.; Higgins, Michael J.; Wang, Zixian
Abstract: Nitrogen oxides and ozone impact air quality in many parts of the United States, Europe, China, and many other countries. The greatest air quality challenge in Los Angeles, some other areas of California, and some parts of China is to reduce ozone levels to meet regulations. Background ozone is a major factor which makes it more difficult to reduce urban concentrations in Los Angeles and some other locations. Air pollution from China affects the background ozone entering California. More than 50 years of history are reviewed with an emphasis on reducing concentrations of nitrogen oxides and ozone. During this time period, there has been significant progress in reducing levels of these pollutants in urban air in the United States and Europe; however, ozone concentrations in China have increased since 2013. Cost and benefit analysis has shown that benefits associated with the Clean Air Act of 1970 have greatly exceeded costs to improve air quality in the U.S. over the past 50 years. Further actions to consider to improve air quality include reducing combustion of coal and petroleum products and transitioning to renewable energy. Public education is recommended to inform citizens that the benefits of reducing emissions far exceed costs.